Cheating is evolutionarily assimilated with cooperation in the continuous snowdrift game. (May 2015) - Sasaki, Tatsuya; Okada, Isamu
Highlights: We fully analyze continuous snowdrift games with quadratic payoff functions in diversified populations. It is well known that classical snowdrift games maintain the coexistence of cooperators and cheaters. We clarify that the continuous snowdrift games often lead to assimilation of cooperators and cheaters. Allowing the gradual evolution of cooperative behavior can facilitate social inequity aversion in joint ventures. Abstract: It is well known that in contrast to the Prisoner's Dilemma, the snowdrift game can lead to a stable coexistence of cooperators and cheaters. Recent theoretical evidence on the snowdrift game suggests that gradual evolution for individuals choosing to contribute in continuous degrees can result in the social diversification to a 100% contribution and 0% contribution through so-called evolutionary branching. Until now, however, game-theoretical studies have shed little light on the evolutionary dynamics and consequences of the loss of diversity in strategy. Here, we analyze continuous snowdrift games with quadratic payoff functions in dimorphic populations. Subsequently, conditions are clarified under which gradual evolution can lead a population consisting of those with 100% contribution and those with 0% contribution to merge into one species with an intermediate contribution level. The key finding is that the continuous snowdrift game is more likely to lead to assimilation of different cooperation levels rather than maintenance of diversity. Importantly, this implies that allowing the gradual evolution of cooperative behavior can facilitate social inequity aversion in joint ventures that otherwise could cause conflicts that are based on commonly accepted notions of fairness.